Maltreatment prevention through early childhood intervention: A confirmatory evaluation of the Chicago Child-Parent Center preschool program - Mersky, Joshua P. (Child Youth Serv Rev, 2011)
Increased recognition of the consequences associated with child maltreatment has led to greater emphasis on its prevention. Promising maltreatment prevention strategies have been identified, but research continues to suffer from methodological limitations and a narrow focus on select prevention models. This investigation uses data from the Chicago Longitudinal Study to examine mediating mechanisms that link the Chicago Child-Parent Center preschool program to a reduction in overall child maltreatment and, more specifically, child neglect. We use structural equation modeling to test child, family, and school measures hypothesized to mediate the effects of CPC participation on maltreatment and neglect. Results indicate that a substantial proportion of the program’s impacts can be accounted for by family support processes, including increased parent involvement in school and maternal educational attainment as well as decreased family problems. The CPC program’s association with reduced school mobility and increased attendance in higher-quality schools also significantly mediated its effects on maltreatment and neglect. Further, a decrease in troublemaking behavior contributed modestly to mediating the program’s association with maltreatment but not neglect. We discuss the implications of these results for the field of maltreatment prevention.